Impact of Telepharmacy on Medication Adherence and Patient Satisfaction: A Literature Review - Hannah Yusriyyah; Rano Kurnia Sinuraya; Auliya Abdurrohim Suwantika (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: Technology has transformed patient care, with telepharmacy emerging as a major advancement. The use of telepharmacy expanded rapidly during and after the COVID-19 pandemic, ensuring continuity of medical care when in-person access was limited. It effectively addresses challenges such as social isolation, restricted facility visits, and the lack of face-to-face consultations. Clinical advantages include improved access to healthcare, reduced costs, higher patient satisfaction, enhanced counseling, and better therapy adherence.Objectives: This literature review aims to the impact of telepharmacy services on medication adherence and patient satisfaction across diverse healthcare settings and patient populations.Methods: A literature search was conducted in PubMed and Scopus using the Boolean operator AND and the keywords "telepharmacy," "adherence," and "satisfaction." The inclusion criteria comprised original articles, published in English between 2015-2025. A total of five articles met these criteria and were included in the review.Results: The reviewed studies consistently demonstrated the benefits of telepharmacy. Among HIV patients, medication adherence reached 100%, while adherence among outpatients with chronic illnesses was 95.2%. Patient satisfaction scores ranged from 9.4 to 9.8 out of 10, or 4.82 out of 5 on Likert scales. Patients particularly valued telepharmacy for its cost-effectiveness, convenience, improved understanding of medications, and continuity of care.Conclusion: Telepharmacy shows strong potential to enhance both patient satisfaction and medication adherence. However, further research is needed to address existing methodological limitations and to better understand its long-term impact and feasibility across various healthcare contexts.